The Influence of Islamic Branding, Religiosity, and Habit on Consumers’ Purchase Decisions of Kula Beauty Halal Cosmetics - Nurfitriah Nurfitriah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
The halal cosmetics industry has experienced rapid growth in line with the increasing awareness of Muslim consumers regarding the importance of using products that comply with Islamic principles. This study aims to analyze the influence of Islamic branding, religiosity, and habit on consumer purchase decisions for Kula Beauty halal cosmetic products. This research employs a quantitative approach using a survey method involving 100 Muslim consumers as respondents. Data were collected through an online questionnaire and analyzed using multiple linear regression analysis with the assistance of SPSS. The results show that Islamic branding, religiosity, and habit simultaneously have a significant effect on consumer purchase decisions. Partially, Islamic branding and habit have a positive and significant effect on purchase decisions, while religiosity does not have a significant effect. These findings indicate that Islamic brand identity and consumption habits play an important role in shaping consumer purchase decisions for halal cosmetic products.